Analisis Anteseden Perilaku Manajemen Finansial Pada Generasi Milenial di Indonesia - Aishuia; Kusnul Fitriani; Farah Margaretha Leon (Fakultas Ekonomi dan Bisnis Universitas Satya Negara Indonesia, 2020)
Millennial generation is identified as materialism, likes credit card promotions, lacks unrealistic knowledge and optimism about the ability to repay debts and has a lifestyle around spending, which follows a